Progress and Challenges of the Sustainable Development Goals in Latin America (Ágora de Heterodoxias, 2025)
Volume 11, Issue 1 of the journal Ágora de Heterodoxias is focused on the analysis of relevant topics linked to Sustainable Development Goals mainly referring to (SDG) 1, 3, 4, 5 and 8 of the 2030 Agenda, established by the United Nations. These goals are fundamental to addressing some of the most pressing challenges facing humanity. As we know, progress on Sustainable Development Goals (SDGs) 1, 3, 4, 5, y 8 in the world and particularly in Latin America, has been mixed, with some progress and several persistent challenges
Keywords: Progress; Challenges; Sustainable Development Goals; Latin America